Teacher Teaching Style Strategies to Improve Student Competency - Muhammad Fachri Fachrezi; M Naufal Rafitaqiyuddin; Euis Latipah (Examinations: Jurnal Pendidikan Guru Sekolah Dasar, 2025)
This study aims to analyze the strategy of teacher teaching style in improving students' competency style in the school environment. The teaching style applied by teachers plays an important role in creating an effective learning atmosphere and arousing students' learning motivation. This study uses a qualitative approach with a case study method conducted in one of the junior high schools. Data collection techniques are carried out through observation, in-depth interviews, and documentation. The results of the study indicate that the application of various teaching styles such as lecture style, jigsaw, and group discussion can increase students' active involvement in learning, encourage creativity, and strengthen conceptual understanding. In addition, strategies that are adaptive to students' needs and characteristics contribute significantly to improving their cognitive, affective, and psychomotor competencies. These findings emphasize the importance of the role of teachers in adjusting their teaching style in order to be able to create meaningful learning and empower students optimally.